Examining the Science Teaching Self-Efficacy Beliefs of Prospective Classroom Teachers in terms of Various Variables - Yildirim, Ramazan; Uyanık, Gökhan (Journal of Computer and Education Research, 2025)
The objective of this study is to examine the science teaching self-efficacy beliefs of prospective classroom teachers according to various variables. The survey model was utilised in the study. The study group consisted of 216 classroom teacher candidates. The data were collected using the Science Teaching Self-Efficacy Belief Scale. Analysis of the findings indicated that the scores of prospective teachers on the Science Teaching Self-Efficacy Belief Scale were above average. When the scores of prospective classroom teachers from the scale were examined according to gender and longest lived residential area variables, it was determined that there was no significant difference. However, a significant difference was detected in the result expectation sub-factor scores of the scale only in terms of grade level variable. Consequently, the outcome expectation sub-factor scores of the second, third and fourth grade prospective teachers were found to be higher than the first grade prospective teachers' scores.